Shooting performance and fly time in highly trained wing handball players: not everything is as it seems - Karcher, C.; Buchheit, M. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To (1) assess the usefulness of countermovement jump (CMJ) testing to predict handball-specific jumping ability and (2) examine the acute effect of transiently modified jumping ability (ie, flight time) on shooting efficiency in wing players.